Asthma and anxiety development in Australian children and adolescents - Garcia, Diana; Darssan, Darsy; Lawler, Sheleigh P; Warren, Christopher M; De Klerk-Braasch, Adel; Osborne, Nicholas J (My University, 2023)
Evidence has suggested a bidirectional association between both the effects and onset of asthma and anxiety. The direction of this association in children and adolescents is less clear. The study evaluates whether anxiety in children is associated with the development of later asthma or, by contrast, whether asthma in children precedes anxiety.
Pediatric Allergy and Immunology
Keywords: anxiety; asthma; atopy; children; longitudinal, LSAC; Adolescents and youth; Childhood and child development; Health and wellbeing